Cool but dirty food? – Estimating the impact of grocery home delivery on transport and CO2 emissions including cooling. (June 2021) - Heldt, Benjamin; Matteis, Tilman; von Schmidt, Antje; Heinrichs, Matthias
Abstract: Recent studies have found that grocery home deliveries are partially replacing consumers' private shopping trips thereby decreasing total vehicle kilometers traveled (VKT) and CO2 emissions. To our knowledge, such studies do not explicitly consider emissions caused by cooling. To assess the impact of home deliveries, we applied a framework consisting of passenger travel demand and delivery tour generation. Applying the models to the city of Berlin, Germany, we compare impacts in scenarios with home delivery from points of sale in the year 2030, assuming two different market shares for e-food and hot and mild air temperatures. The results show that home delivery decreases VKT and emissions, but total CO2 emissions are much higher when food cooling is included in hot scenarios and moderately higher or decreasing in mild scenarios as refrigerator units increase fuel consumption and, thus, freight transport emissions by factor two to five as compared to driving. Urban areas are more affected by adverse effects while remote and less dense areas benefit. These findings show the need for considering cooling in analyses of the effects of grocery home delivery and call for the use of more energy-efficient and less polluting technologies in delivery vehicles for driving and chilling.